PENGARUH ETHICAL LEADERSHIP, ETHICAL CLIMATE DAN AFFECTIVE COMMITMENT TERHADAP WORK ENGAGEMENT DI LINGKUNGAN SEKERTARIAT JENDERAL KEMENTERIAN PERINDUSTRIANREPBULIK INDONESIA - Cut Alanda Deshire, - (2022)
Work engagement is one of the main strategies for managing human resources today even though the reality shows that the number of employees who are engaged in their work in Indonesia and even in the world is still relatively low, as well as its growth. This study aims to determine the effect of ethical leadership, ethical climate, and affective commitment on work engagement and the role of affective commitment as a mediating variable through 83 employees as respondents in the Secretariat General of the Ministry of Industry. The research instrument used the work engagement scale, ethical leadership scale, ethical climate questionnaire, and affective commitment scale, all of which were adapted to the needs of this study. The research approach is a quantitative method with analysis using Smart PLS 3.0. The research findings prove that ethical leadership, ethical climate, and affective commitment have a positive and significant effect on work engagement. Further results reveal that ethical leadership and ethical climate have no effect through the mediating variable of affective commitment to work engagement. The quality of leaders who are fair, exemplary, and integrity contributes greatly to the influence of ethical leadership on work engagement, while the law and codes climate is the biggest contributor to the influence of ethical climate on work engagement, while the sense of belonging and loyalty are the strongest factors of affective commitment that affect work engagement.